- 5 - x + 2 - x + 6 - x + 10 - x = -5 + 2 + 6 + 10 - x - x - x - x = 13 - 4x
-2 and -6
If: x+2 = y+6 Then: y = x-4
x^2 +7x+6 = (x+1)(x+6) when factored
x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)
x+x+2+x+4+x+6=42(x+x+x+x)+(2+4+6)=424x+12=424x=30x=15/2or 7 and 1/2
5x+1+x-2 = 8x+6 5x+x-8x = 6+2-1 -2x = 7 x = -3.5
7x + 6
x2 + 8x + 12 = (x + 6) (x + 2)
x^2 + 12x + 36 = 0(x + 6)(x + 6) = 0(x + 6)^2 = 0√(x + 6)^2 = ± √0x + 6 = 0x + 6 - 6 = 0 - 6x = 6
6^3 + 2^4 = (6 x 6 x 6) + (2 x 2 x 2 x 2) = 216 x 16 = 3456
-5x+2=-6+x therefore -5x+2+6=x therefore 2+6=x+5x therefore 8=6x therefore 8/6=x therefore x=4/3=1.3333
(x + 6)(x + 2)
2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)
2/3 +x= 4/6 4/6+x=4/6 x=0
The sum 6 (3x^2) + 8x -3 plus 3 (3x^2) - 7x + 2 = 27 x^2 + x -1
2(x + 6)(x + 3)